Wild meat consumption in urban Sierra Leone during the Covid-19 pandemic - Sainge, M.N.; Wusha-Conteh, F.; Fa, J.E.; Sullivan, M.J.; Cuní-Sanchez, A. (Cambridge University Press, 2023)
Wild meat is associated with an increased risk of zoonotic diseases. In some West African countries wild meat consumption declined as the result of official restrictions following Ebola outbreaks during 2013–2016, and was also affected by the current Covid-19 pandemic. In Sierra Leone, a country affected by these diseases, we documented wild meat use in four markets in the capital, Freetown. From a total of 197 interviews, we analysed the influence of age and gender on the types of wild meat eaten and the reasons for their consumption. We found that more men than women consumed wild meat, and for both genders taste was the main reason for eating wild meat. Age did not affect wild meat consumption amongst women. Evidence for changes in consumer behaviour in response to zoonotic disease risk was mixed. Although some consumers avoided wild meat because of disease risk, none stated this was the primary reason for not eating wild meat, and monkeys (presumed to carry a high zoonotic disease risk) were amongst the species cited as being consumed often. More work is needed to identify the best pathway towards safe and sustainable consumption of wild meat in urban Sierra Leone.